Pelaksanaan Pendampingan Belajar Siswa Melalui Gerakan Literasi Digital Secara Daring - Rizkha Dwi Putri Aprilyani1; Zahra Benayya Putri; Susilawati Susilawati (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
During the COVID-19 pandemic, all activities have been diverted at home, including schools. Learning activities at school or referred to as online learning of course use online classes in practice. The use of information technology in the world of education provides a digital platform to support online learning. For this reason, the digital literacy movement is deemed appropriate to be implemented. Qualitative writing method with data presentation in the form of description/narrative. In collecting data, grade 2 students at SDN Sumur Batu 14 Pagi were used as objects in learning assistance activities in the context of community service through the 2021 UPI Thematic KKN education. This learning assistance was carried out through the digital literacy movement with a learning system while playing interactive games such as quizizz. The results of student learning assistance carried out by the author, students feel happy and happy in learning and learning evaluation is increasing